INFORMATION SYSTEM DEVELOPMENT AND MANAGEMENT: A HANDS ON PRACTICE - Gul, Fahad Ali; Bertozzi, Federica; Ali, Chauhdry Mehr (International Journal For Research In Business, Management And Accounting, 2018)
Nowadays, information systems are the key to organizational success if not the only chance to survival. In a world that is moving towards e-business and m-commerce being able to satisfy the customer need for a fast, social and pleasant experience leads directly back to the roots of organizational daily transactions and business processes. The optimization and automation of these routinely activities, along with more correct previsions, will allow organizations to be more competitive on a global scale in matter of products and services, as well as more advantaged in handling and using information for the organizational growth.